2017
DOI: 10.1016/j.intell.2017.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Network connectivity correlates of variability in fluid intelligence performance

Abstract: Abstract\ud Abstract reasoning requires a pattern of spatial and temporal coordination among regions across the entire brain. Recent evidence suggests a very high similarity between spontaneous and evoked brain activity in humans, implying that a fine characterization of brain dynamics recorded during resting-state might be informative for the understanding of evoked behavior. In a recent work, we listed and detailed the sets of regions showing robust co-activation during the solution of fluid intelligence (gf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
35
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 59 publications
(46 citation statements)
references
References 86 publications
9
35
0
Order By: Relevance
“…Several studies have also investigated the impact of tDCS by combining TMS‐EEG (Pellicciari et al., 2013; Romero Lauro et al., 2014; Varoli et al., 2018) or by means of neuroimaging measures (Amadi, Ilie, Johansen‐Berg, & Stagg, 2014; Polanía, Paulus, & Nitsche, 2012a, 2012b; Sehm, Kipping, Schäfer, Villringer, & Ragert, 2013). Given the shift in focus toward network‐based approaches for the study of human cognition (Pisoni et al., 2018; Santarnecchi et al., 2017; Santarnecchi, Momi, et al., 2018; Santarnecchi, Sprugnoli, et al., 2018; Spreng et al., 2016) —and more recently even for the diagnosis of neuropsychiatric conditions (Fox et al., 2014)— we tested the impact of a tDCS montage optimized to concurrently modulate multiple nodes of the SMN (and its negatively correlated regions) instead of just left M1. Using a multifocal tDCS solution previously tested by our group (Fischer et al., 2017), here we document a greater modulation of FC involving both left and right M1 during net‐tDCS compared to standard tDCS, similar to that observed in our previous study where an increase in excitability of right M1 was found solely for net‐tDCS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have also investigated the impact of tDCS by combining TMS‐EEG (Pellicciari et al., 2013; Romero Lauro et al., 2014; Varoli et al., 2018) or by means of neuroimaging measures (Amadi, Ilie, Johansen‐Berg, & Stagg, 2014; Polanía, Paulus, & Nitsche, 2012a, 2012b; Sehm, Kipping, Schäfer, Villringer, & Ragert, 2013). Given the shift in focus toward network‐based approaches for the study of human cognition (Pisoni et al., 2018; Santarnecchi et al., 2017; Santarnecchi, Momi, et al., 2018; Santarnecchi, Sprugnoli, et al., 2018; Spreng et al., 2016) —and more recently even for the diagnosis of neuropsychiatric conditions (Fox et al., 2014)— we tested the impact of a tDCS montage optimized to concurrently modulate multiple nodes of the SMN (and its negatively correlated regions) instead of just left M1. Using a multifocal tDCS solution previously tested by our group (Fischer et al., 2017), here we document a greater modulation of FC involving both left and right M1 during net‐tDCS compared to standard tDCS, similar to that observed in our previous study where an increase in excitability of right M1 was found solely for net‐tDCS.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the negative connectivity (or “anticorrelation”) between brain networks has been also promoted as a crucial aspect of the functional organization of the human brain, with relevance for cognitive performance (Fox et al., 2005). For instance, recent reports have highlighted how the strength of the negative connectivity between regions of the dorsal attention network (DAN) and the DMN is among the best predictors of individual variability in intelligence levels (Santarnecchi et al., 2017). Recent work by our group has shown the possibility to selectively modify resting‐state fMRI network‐to‐network coupling by means of multisite TMS using cortico‐cortical paired associative stimulation (cc‐PAS; Santarnecchi, Momi, et al., 2018); however, the possibility to modulate inter‐network dynamics by means of network‐targeted tDCS has not been demonstrated yet.…”
Section: Discussionmentioning
confidence: 99%
“…Even though previous studies have reported deactivation coordinates for single analysis, to the best of our knowledge here we originally provide an ALE map showing the neural deactivation during the n-back task, revealing a signifi- In line with the "deactivation of the DMN," we identified a high resemblance between the connectivity profile of regions activated during n-back processing and the DAN. Interestingly, the interplay between these two networks has been suggested as a major candidate biomarker for normal and pathological aging (Spreng & Schacter, 2012;Spreng, Stevens, Viviano, & Schacter, 2016) and has been correlated with cognition in healthy young participants Santarnecchi, Emmendorfer, Tadayon, et al, 2017). A clear overlap with DMN and DAN can suggest the modulation of their interplay as a candidate target for brain stimulation interventions based on transcranial magnetic stimulation (TMS) and transcranial electrical stimulation (tES), able to modulate network-level activity and elicit cognitive enhancement (Ruffini, Wendling, Sanchez-Todo, & Santarnecchi, 2018;Santarnecchi et al, 2018).…”
Section: Functional Connectivity Profile Of Neural Activation and Dmentioning
confidence: 99%
“…A consistent finding is that functional and structural brain networks with higher global efficiency, i.e. networks with shorter connections between any pair of nodes in the network, are associated with higher scores on assessments of general intelligence in both children and adults (Santarnecchi et al 2017; Pineda-Pardo et al 2016; Kim et al 2016; van den Heuvel et al 2009).…”
Section: Introductionmentioning
confidence: 71%